2015
DOI: 10.1002/jhm.2447
|View full text |Cite
|
Sign up to set email alerts
|

The impact of emergency department observation units on United States emergency department admission rates

Abstract: OBJECTIVE: Prior studies suggesting that the presence of emergency department (ED) observation units decrease overall ED hospital admissions have been either singlecenter studies or based on model simulations. The objective of this preliminary national study is to determine if the presence of ED observation units is associated with hospitals having lower ED admission rates. METHODS:We conducted a retrospective cross-sectional analysis using the 2010 National Hospital Ambulatory Care Survey and estimated ED ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Others have studied the use of EDOUs, typically structured as an ED or inpatient unit but designed for patients who need more than an initial ED workup, but less than 24 hours of observation or evaluation. These can be lower cost (to the healthcare system) than an inpatient admission, and are increasing in popularity in the U.S. 23 Some have found that these EDOUs can minimize inpatient admission for lower risk TIA patients in a safe manner. 19 , 22 Our results are consistent with these findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have studied the use of EDOUs, typically structured as an ED or inpatient unit but designed for patients who need more than an initial ED workup, but less than 24 hours of observation or evaluation. These can be lower cost (to the healthcare system) than an inpatient admission, and are increasing in popularity in the U.S. 23 Some have found that these EDOUs can minimize inpatient admission for lower risk TIA patients in a safe manner. 19 , 22 Our results are consistent with these findings.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 21 , 22 While less common in other countries, EDOUs are increasingly used in the U.S. for patients who require more than a brief ED stay but less than 24 hours of observation or urgent diagnostics. 23 Our EDOU was managed by a nurse practitioner (NP) who was empowered to guide patients who would likely require more than 24 hours for their workup, based on availability of hospital resources at the time. In this analysis, we evaluated whether we could use this pathway to provide consistent streamlined care with shorter LOS without increasing 90-day stroke risk.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, ED-Obs units are increasingly utilized for COPD patients as a short-term 24-to 36-hour stay for evaluation and treatment before deciding the final disposition. 9,21 In an ideal situation ED-Obs setting is best utilized to treat non-life-threatening eCOPD that require short-term monitored care to ensure patient safety and potentially prevent costly hospitalization. A subset of these patients will, however, end up requiring hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…1 Emergency departments are using observation units as efficient modalities for implementing clinical pathways that allow for more rapid evaluation, testing, treatment, and disposition of patients while avoiding inpatient hospital admission. [2][3][4] A significant number of patients who present to the ED may be unsafe to return home in their current state-whether it be from a fall, deconditioning, or illness-and could benefit from evaluation by a physical therapist. Traditionally, once emergent conditions requiring inpatient hospitalization and treatment were excluded in the ED, these patients were admitted to the hospital primarily for evaluation by a physical therapist.…”
Section: Introductionmentioning
confidence: 99%